Comparison of body fat results from 4 bioelectrical impedance analysis devices vs. air displacement plethysmography in American adolescent wrestlers - Montgomery, M. M.; Marttinen, R. H.; Galpin, A. J. (International Journal of Kinesiology & Sports Science, 2017)
Accurate and accessible methods of body composition are necessary to ensure health and safety of wrestlers during competition. The most valid and reliable instruments are expensive and relatively inaccessible to high school wrestlers; therefore, more practical technology is needed. Objective: To compare body fat percentage (BF%) results from 4 bioelectrical impedance analysis (BIA) devices to those from air displacement plethysmography (ADP) in adolescent wrestlers. Methodology: 134 adolescent male and female wrestlers (1.72±0.9 m, 66.8±14.3 kg, 15.6±1.1 yrs.) were tested for hydration and then completed 4 body composition tests with different BIA devices and one with Bod Pod. Relative and absolute agreement were assessed between each BIA device and ADP on a single day. Results: When compared with ADP, all devices demonstrated excellent reliability (ICC (2,1)) range: 0.88-0.94), but questionable measurement error (SEM range: 2.3-3.6 %BF). Bland-Altman plots revealed that each bioelectrical impedance device we tested over-estimated body fat percent in high school wrestlers (range: 0.8-3.6 %BF) and demonstrated wide 95% limits of agreement (range: 15.0-20.8 %BF) compared to ADP. Conclusions: The devices investigated demonstrated reasonable measurement accuracy. However, wide margins of error of each device were noted. Caution should be taken when assessing adolescent wrestlers with lower amounts of body fat, as it may result in failing to identify those who do not meet the minimum body fat percentage for competition. The governing bodies should use the research data in the decision-making process regarding appropriate devices for use in their weight management programs.